ОПЕРАТИВНЕ ДІАГНОСТУВАННЯ ВИСОКОВОЛЬТНОГО ОБЛАДНАННЯ В ЗАДАЧАХ ОПТИМАЛЬНОГО КЕРУВАННЯ РЕЖИМАМИ ЕЛЕКТРОЕНЕРГЕТИЧНИХ СИСТЕМ - Лежнюк , П.Д.; Рубаненко, О.Є.; Нікіторович , О.В. (Інститут електродинаміки НАН України, Київ, 2012)
Povrezhdaemost of autotransformers is investigational and methodology of determination of coefficient of their remaining resource is offered in the conditions of incompleteness of initial data. Formulas which allow to find the forecast value of this coefficient on current values one and by the retrospective values of other diagnostic parameters are got. Influence of account of the state of high-voltage equipment is considered on the choice of the technical providing of process of optimum management the modes of the electroenergy systems. References 2.